Estudo do efeito da fração não dialisável do látex de Calotropis procera (ait) R. Br em modelos experimentais de inflamação, com ênfase em artrite - Cavalcante, Cid Freitas (2007)
The objective of this dissertation was to investigate the effect of the latex from Calotropis procera in experimental models of inflammation, with special focus on arthritis. The plant belongs to Asclepiadaceae family and is largely found in Northeast of Brazil. The plant latex presents clear anti-inflammatory effects, which is kept by its non-dialyzable protein fraction (NDPF), a less toxic and rubber free fraction. NDPF was obtained according to a procedure established by our group, which, in short, involves several steps of centrifugation and dialysis. Male Wistar rats (230 – 280g) and Balb/c and Swiss male mice (18 – 35g) were organized in groups of 6 animals: a control group (no treatment), a sham group, in which only the inflammatory event was induced (arthritis by zymosan – AZy), an antigen-induced arthritis group (AIA), an infectious peritonitis group (IP) and an experimental group, treated with NDPF. The AZy group was submitted to an articular incapacitation test to measure the paw elevation time (PET, in seconds) and, after sacrifice, total and differential cell count in the intra-articular fluid, histopathological study of the articulation, vascular permeabilization, ADA and TNF-α assays. The results were expressed in means + S.E.M. and significative differences were accepted if p<0.05 (ANOVA/Bonferroni). NDPF inhibited PET in AZy with a maximum effect in the dose of 3mg/kg, at 4h after inflammation induction. There was also a significative reduction of vascular permeability, TNF-α and ADA serum levels and an improvement of the histopathological profile. NDPF also reduced the intra-articular influx of cells in AZy and AIA, especially of neutrophils. In IP, NDPF inhibited the cellular migration and the levels of ADA. So, the results confirmed the expected anti-inflammatory effect of NDPF in arthritis and peritonitis models and suggested a possible mechanism of action involving either an increase of adenosine concentration due to the reduction of ADA levels or an inhibition of TNF-α or both events. Finally, the NDPF chronical toxicity was evaluated confirming that the dose of 10mg/Kg presents well defined pharmacological effects without significant alterations on the animal parameters. The characteristics of NDPF open an interesting possibility for alternative therapy to substitute the toxic effects of steroidal and some non-steroidal drugs, used in rheumatoid diseases, so prevalent among our population.